Can agglomeration of producer services reduce urban–rural income inequality? The case of China. (23rd March 2021) - Zhao, Jun; Dong, Xiucheng; Dong, Kangyin
Abstract: In this study, we construct a theoretical model and investigate the impact of agglomeration of producer services (APS) on urban–rural income inequality in China. The mediating effects are explored. Results indicate that the growth of APS can not only narrow China's urban–rural income gap directly, but also have an indirect negative effect on income inequality by promoting urbanisation evolution and human capital accumulation. Furthermore, the agglomeration of six sub‐industries is conducive to reducing the income gap. Among them, the agglomeration of the traffic, transport, storage and post has the greatest effect, while the effect of information transfer, computer services and software agglomeration is not significant. In addition, the results of regional heterogeneity show that only in the low APS region can APS and income inequality show bidirectional causality.